2002
DOI: 10.1093/ndt/17.8.1470
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of volume of blood processed on haemodialysis adequacy measurement sessions vs regular non-adequacy sessions

Abstract: This study demonstrates that the average VBP is less on non-URR than on URR measurement days; this difference was clinically important in >20% of patients. Univariate analysis indicated that the use of a fistula or graft correlated with a higher DeltaVBP(U)(-N). This implies that our current method of assessing dialysis adequacy does systematically overestimate the average delivered dose of dialysis in a subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…[19] Brimble et al used the volume of blood processed (VBP) as a surrogate marker of delivered dialysis, and compared VBP on days adequacy was measured to days it was not. [20] They found that more than 20% of patients had a significant reduction in VBP on the days adequacy was not assessed. [20] K ID t/V ID is an alternative method that clinicians may use to follow adequacy during each dialysis session; additionally, K ID t/V ID may enable clinicians to follow total weekly or monthly Kt/V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19] Brimble et al used the volume of blood processed (VBP) as a surrogate marker of delivered dialysis, and compared VBP on days adequacy was measured to days it was not. [20] They found that more than 20% of patients had a significant reduction in VBP on the days adequacy was not assessed. [20] K ID t/V ID is an alternative method that clinicians may use to follow adequacy during each dialysis session; additionally, K ID t/V ID may enable clinicians to follow total weekly or monthly Kt/V.…”
Section: Discussionmentioning
confidence: 99%
“…[20] They found that more than 20% of patients had a significant reduction in VBP on the days adequacy was not assessed. [20] K ID t/V ID is an alternative method that clinicians may use to follow adequacy during each dialysis session; additionally, K ID t/V ID may enable clinicians to follow total weekly or monthly Kt/V.…”
Section: Discussionmentioning
confidence: 99%
“…Several contributors to the discussion of on-line clearance monitoring were concerned that a single monthly check on dialysis dose could be misleading. Knowing that the blood tests are due could mean staff take extra care to have the right blood flow and the full treatment time [14].…”
Section: Summary Of the Edtna|erca Journal Club Discussion Summer 2006mentioning
confidence: 99%
“…The clustering of URR values to facilities are reported by some as reflective of facility‐specific URR sampling practices . Evidence suggest that facility URRs largely overestimate clearances provided; when blood volume processed is measured, it is higher on URR draw days than other days, and depends more on nursing factors than patient factors . Keeping blood flow rates above 350 mL/min, in one study, was effective in improving outcomes, especially in women and older individuals .…”
Section: Stakeholder‐level Risks To Hospitalizations In Patient On Hementioning
confidence: 99%
“…[130][131][132] Evidence suggest that facility URRs largely overestimate clearances provided; when blood volume processed is measured, it is higher on URR draw days than other days, and depends more on nursing factors than patient factors. [132][133][134] Keeping blood flow rates above 350 mL/min, in one study, was effective in improving outcomes, especially in women and older individuals. 62 Neither vascular access surveillance nor recirculation measurements (important to maintaining good clearances) are routinely carried out or are inaccurately performed.…”
Section: Psychosocialmentioning
confidence: 99%